"For lack of knowledge, our people will perish": Using focus group methodology to explore African-American communities' perceptions of breast cancer and the environment. (December 2018) - Lewis, Kaleea; Kulkarni, Shibani; Adams, Swann Arp; Brandt, Heather M.; Lead, Jamie R.; Ureda, John R.; Fedrick, Delores; Mathews, Chris; Friedman, Daniela B.
Abstract: Among women living in the United States, breast cancer is the second leading cause of cancer death. Disproportionate racial disparities in breast cancer exist, with African American (AA) women consistently having the highest rates of breast cancer related mortality despite lower incidence. This study attends to the Institute of Medicine's (IOM) call to action recommending the identification of effective strategies for communicating accurate and reliable breast cancer risk information to diverse audiences. Using focus group methodology, this study explores how AAs perceive and decipher information related to breast cancer and its relationship to their environment. Six focus groups were conducted. The sample (n = 50) was African American, 98% female, with an average age of 50.1 years. The focus group protocol consisted of open-ended questions designed to elicit information about participants' perceptions of their environment and its link to breast cancer. Focus groups were audio recorded and professionally transcribed. Analysis of the focus group transcripts revealed themes pertaining to these categories: (1) general knowledge and beliefs about breast cancer, (2) perceived environmental risks factors for breast cancer, (3) importance of seeking knowledge about breast cancer and the environment, and (4) recommended communication strategies. The emergent themes reflect the knowledge participants possessed about breast cancer and environmental risk factors, in addition to concerns about the importance of possessing accurate information, and how culturally appropriate health communication strategies can be used to disseminate breast cancer knowledge in the community. Findings from this study can be used for culturally appropriate communication about breast cancer and the environment with AA communities. Highlights: Culture may influence perceptions about breast cancer risk. Participants stressed the importance of having knowledge about environmental risks. Communities' cancer perceptions can guide culturally appropriate education.